Hope and Resilience Among Pre-Championship Athletes with Disabilities - Scarvanovi, Berliana Widi; Agustinab, Laelatus Syifa Sari; Hidayatic, Farida (Journal of ICSAR, 2020)
Physical limitations do not become obstacles for people with disabilities to become creative and get the achievement. The persons with disabilities to be creative and achieve in sports. Sports is the media that can be a means of self-actualization for athletes with physical disabilities. Therefore the match can reduce a stressful event for athletes with a physical disability. This study aims to see the correlation between hope and resilience among pre-championship athletes with disabilities. This study's population is pre-championship of the athlete with disabilities trained under NPC (National Paralympic Committee) of Indonesia. The participants of this research are 112 athletes. The current study was finding a correlation of hope and resilience among pre-championship athletes with disabilities. The contribution of hope to resilience is 51%, while other variables influence the other 49%. Furthermore, hope has a strong positive correlation to resilience.